Investigating the efficacy of attention bias modification in reducing high spider fear: The role of individual differences in initial bias - Fox, E; Zougkou, K; Ashwin, C; Cahill, S (Elsevier, 2015)
Background and objectives Attention Bias Modification (ABM) targets attention bias (AB) towards threat and is a potential therapeutic intervention for anxiety. The current study investigated whether initial AB (towards or away from spider images) influenced the effectiveness of ABM in spider fear. Methods AB was assessed with an attentional probe task consisting of spider and neutral images presented simultaneously followed by a probe in spider congruent or spider incongruent locations. Response time (RT) differences between spider and neutral trials > 25 ms was considered ‘Bias Toward’ threat. RT difference < - 25 ms was considered ‘Bias Away’ from threat, and a difference between −25 ms and +25 ms was considered ‘No Bias’. Participants were categorized into Initial Bias groups using pre-ABM AB scores calculated at the end of the study. 66 participants' (Bias Toward n = 27, Bias Away n = 18, No Bias n = 21) were randomly assigned to ABM-active training designed to reduce or eliminate a bias toward threat and 61 (Bias Toward n = 17, Bias Away n = 18, No Bias n = 26) to ABM-control. Results ABM-active had the largest impact on those demonstrating an initial Bias Towards spider images in terms of changing AB and reducing Spider Fear Vulnerability, with the Bias Away group experiencing least benefit from ABM. However, all Initial Bias groups benefited equally from active ABM in a Stress Task. Limitations Participants were high spider fearful but not formally diagnosed with a specific phobia. Therefore, results should be confirmed within a clinical population. Conclusions Individual differences in Initial Bias may be an important determinant of ABM efficacy.